PENGARUH KOMPETENSI GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI (STUDI PADA GURU SD NEGERI DABIN III DI KECAMATAN PATI KABUPATEN PATI) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research was aimed to examine the influence of teacher competence and work motivation toward the performance of Primary teachers moderated by Organizational Culture in Pati the District. Population of 106 people, after Slovin formula used a sample of 79% or about 84 people from the total sample, sampling using random sampling. Data collecting is done by questionnaire required by the respondent. Data analysis uses the regression analysis. The results of this research show that the competence of teachers (X1) has significant positive effect on teacher performance (Y). Motivation (X2) has also significant positive effect on teacher performance (Y). While in moderation test in this study are moderated by Cultural Organization (Z) variables can be stated that the Teacher Competency (X1) of the Teacher Performance (Y) with moderated Cultural Organization (Z) with Z as a result of research Variable Moderating. To Influence Motivation (X2) on Teacher Performance (Y) which is moderated by the effect of Cultural Organization (Z) is not significant and not as a moderating variable. Keywords: Competence of Teachers, Teacher’s Motivation and Teacher’s Performance as well Organizational Culture